Blockchain-enabled transparent traffic enforcement for sustainable road safety in cities - Chen, Chin-Ling; Tu, Cheng-Yang; Deng, Yong-Yuan; Huang, Der-Chen; Liu, Ling-Chun; Chen, Hsing-Chung (Frontiers in Sustainable Cities, 2024)
Global concern for road safety has prompted nations to deploy cross-border traffic law enforcement systems, pivotal in reducing accidents and curbing reckless driving. However, a significant impediment threatens their efficacy: corruption. The shadow of corruption casts doubt on mechanisms designed to safeguard lives on roads. According to the World Health Organization (WHO), car accidents claim nearly 1.3 million lives annually, with 20 to 50 million sustaining non-fatal injuries. Countries respond by implementing traffic laws and leveraging electronic technology to enhance enforcement, such as speed cameras, smart contracts, and blockchain techniques for distributed A.I. (Artificial Intelligence). Despite improvements, challenges persist, including blurred images and misjudgments by police agencies. Instances of exploiting vulnerabilities in the traffic law enforcement framework reveal a disconcerting reality where some evade consequences through bribery or connections, exacerbating accidents and leaving victims and families grappling with the aftermath. A critical reevaluation of road safety approaches is imperative, necessitating innovative solutions to address system shortcomings and resist corruption. We propose a datatraceability law enforcement system based on blockchain and IPFS. This system ensures quick traceability and protects law enforcement data from external attacks. Leveraging blockchain's decentralized nature and smart contract aims to instill accountability and fairness in road safety initiatives, mitigating the impact of corruption and paving the way for a safer, more just transportation landscape. Our experimental results show that under our stress test of 50 transactions per second, the throughput can be as high as 300, and the maximum delay reaches 2.01 seconds. The experiment proves that the system is feasible.